A gradient wetting multilayer metal mesh composite material and its preparation method and application
By forming a multi-layer structure on the metal mesh, including metal anti-corrosion transition layer and micro-nano porous layer, and distributing superhydrophilic metal oxides on the surface and inner walls of the holes, the corrosion resistance, hydrophilicity and capillary force of the metal mesh is solved. The limitations of the aspects achieve efficient water storage and capillary capacity, and are suitable for a variety of applications.
Patent Information
- Application Number
- CN202411214891.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-02
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-09-02
AI Technical Summary
The limitations of metal mesh in corrosion resistance, hydrophilicity and capillary force restrict their effectiveness and scope of application in certain key applications.
Gradient wetting multi-layer metal mesh composite material is used, which consists of a metal mesh substrate, a metal anti-corrosion transition layer and a metal porous layer with a micro-nano porous structure. Superhydrophilic metal oxides are distributed on the surface and inner walls of the holes.
It has achieved excellent super hydrophilicity, water storage capacity and capillary capacity of composite materials, and is suitable for the fields of liquid absorbent core of the heat-smooth plate and oil-water separation.
Smart Images

Figure CN118756279B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydrophilic materials, and in particular relates to a gradient wetting multilayer metal mesh composite material and a preparation method and application thereof. Background Art
[0002] As a high-performance material, metal mesh has shown great application potential in many fields due to its unique physical and chemical properties. The high porosity, large specific surface area and good mechanical strength of metal mesh make it an ideal adsorption material, filter medium and heat dissipation component, playing an important role in sewage treatment, oil-water separation, heat sink and liquid absorption core of electronic equipment.
[0003] However, the limitations of metal mesh in terms of corrosion resistance, hydrophilicity and capillary force have, to a certain extent, restricted its effectiveness and applicability in certain key applications. Summary of the invention
[0004] In order to solve all or part of the above technical problems, the present invention provides the following technical solutions:
[0005] One of the purposes of the present invention is to provide a gradient wetting multilayer metal mesh composite material, comprising:
[0006] A metal mesh substrate having a mesh structure formed of metal;
[0007] A metal anti-corrosion transition layer is coated on the metal mesh substrate;
[0008] The metal porous layer is covered on the metal anti-corrosion transition layer and has a micro-nano porous structure, and super-hydrophilic metal oxides are distributed on the surface of the metal porous layer and the inner wall of the holes of the micro-nano porous structure.
[0009] The super-hydrophilic metal oxides on the surface and pore inner walls of the composite material provided by the present invention give the composite material excellent super-hydrophilicity, and the complementary advantages of each functional layer and multifunctional coupling give the composite material excellent water storage capacity and capillary capacity, so that water molecules can be hydrophilically adsorbed on the surface of the composite material and transported and stored in the micro-nano porous structure to form a gradient wetting structure; the composite material is suitable for preparing heat spreader wicks, oil-water separation and other fields.
[0010] In some embodiments, the average pore size of the pores contained in the micro-nano porous structure is 50-1000 nm.
[0011] In some embodiments, the porosity of the metal porous layer is 20-90%.
[0012] In some embodiments, the thickness ratio of the metal mesh substrate and the metal anticorrosion transition layer is 1-100: 0.1-10, and the thickness ratio of the metal anticorrosion transition layer to the metal porous layer is 0.1-10: 1-20. The present invention has systematically studied and found that when the thickness ratio of the three layers is within the above range, a composite material with good bonding and appropriate porosity can be obtained. If the metal porous layer is thin, the water storage capacity and capillary capacity are insufficient. If the metal porous layer is too thick, the porous layer is prone to collapse.
[0013] In some embodiments, the thickness of the metal mesh substrate is 50-200 μm.
[0014] In some embodiments, the thickness of the metal anti-corrosion transition layer is 0.5-50 μm.
[0015] In some embodiments, the thickness of the porous metal layer is 5-100 μm.
[0016] In some embodiments, the thickness ratio of the super hydrophilic metal oxide on the surface of the metal porous layer to the metal porous layer is 0.1-1:5-100. When the content of the hydrophilic metal oxide attached to the metal porous layer is within the above range, the composite material can be endowed with good hydrophilicity.
[0017] In some embodiments, the diameter of the mesh holes contained in the metal mesh substrate is 120-500 meshes.
[0018] In some embodiments, the metal mesh substrate is made of stainless steel, or one or more of copper, iron, and chromium.
[0019] In some embodiments, the material of the metal anti-corrosion transition layer includes nickel. Nickel has good corrosion resistance, and the metal porous layer formed on the nickel base has good bonding strength.
[0020] In some embodiments, the material of the metal porous layer includes copper. The porous copper layer has good thermal conductivity, suitable deposition efficiency, and easy surface wettability modification.
[0021] In some embodiments, the superhydrophilic metal oxide includes copper oxide.
[0022] In some embodiments, the contact angle between the surface of the gradient wetting multi-layer metal mesh composite material and water is 0°.
[0023] The second object of the present invention is to provide a method for preparing a gradient wetting multilayer metal mesh composite material, comprising:
[0024] Providing a metal mesh substrate, and forming a metal anti-corrosion transition layer on the metal mesh substrate to obtain a first intermediate material;
[0025] At least using an electrodeposition method to form a polymer microsphere composite metal layer on the first intermediate material to obtain a second intermediate material, wherein the polymer microsphere composite metal layer includes a metal material layer and polymer microspheres, and the polymer microspheres are distributed on the surface and inside of the metal material layer;
[0026] At least the second intermediate material is sintered to remove the polymer microspheres, forming a porous metal layer with a micro-nano porous structure, and simultaneously forming a super-hydrophilic metal oxide on the surface of the porous metal layer and on the inner wall of the pores of the micro-nano porous structure to obtain a gradient wetting multilayer metal mesh composite material.
[0027] The polymer microsphere composite metal layer formed in the preparation method is a metal layer containing polymer microspheres, the polymer microspheres are embedded in the metal layer, and the surface of the metal layer may also have partially exposed polymer microspheres embedded therein; the second intermediate material is sintered to remove the polymer microspheres to form a pore structure with a particle size of the polymer microspheres. During the sintering process, the metal in the polymer microsphere composite metal layer or the porous metal layer is converted into a super-hydrophilic metal oxide; and the polymer microspheres in the micro-nano porous structure are removed at high temperature to form a super-hydrophilic metal oxide on the pore wall, thereby improving the hydrophilicity of the composite material. Compared with the method of directly covering the metal porous layer with a hydrophilic layer or directly filling the porous structure with a hydrophilic substance, the preparation method provided by the present invention forms a metal oxide hydrophilic structure in situ by heating, does not need to be modified by multiple processes, is easier to mass produce, and the super-hydrophilic oxide formed in situ is not easy to fall off and is evenly distributed; in particular, the sintering treatment can form an appropriate amount of super-hydrophilic oxide on the inner wall of the hole (the thickness of the hydrophilic oxide on the inner wall of the hole is about 0.8% to 8% of the hole radius) while maintaining a good micro-nano porous structure, so that the composite material has both hydrophilicity, water storage capacity and capillary capacity.
[0028] In some embodiments, the metal mesh substrate is made of stainless steel, or one or more of copper, iron, and chromium.
[0029] In some embodiments, the particle size of the polymer microspheres is 50-1000 nm.
[0030] In some embodiments, the material of the polymer microspheres includes polystyrene.
[0031] In some embodiments, the sintering temperature is lower than the melting point of the metal in the metal mesh substrate, the metal anti-corrosion transition layer and the polymer microsphere composite metal layer, and can remove the polymer microspheres.
[0032] In some typical embodiments, the process conditions of the sintering treatment include: a sintering temperature of 300-700° C. and a sintering time of 30-300 min.
[0033] In some embodiments, the method of coating the metal anti-corrosion transition layer on the metal mesh substrate includes, but is not limited to, an electrodeposition method. In particular, when the material of the metal mesh substrate is stainless steel, the nickel metal anti-corrosion transition layer formed by electrodeposition impact plating has better bonding strength, which is conducive to the deposition and bonding of the subsequent porous layer.
[0034] In some embodiments, the step of coating the metal anti-corrosion transition layer on the metal mesh substrate specifically includes: using the metal mesh substrate as a first cathode and placing it together with a first anode in a first electroplating solution to perform a first electrodeposition reaction, wherein the first electroplating solution includes a soluble salt of a first metal, an acid and a surfactant.
[0035] In some embodiments, the first electroplating solution contains 5-25 wt % of a soluble salt of a first metal, 2-15 wt % of a first acid, and 0.01-1 wt % of a surfactant.
[0036] In some embodiments, the soluble salt of the first metal includes a soluble salt of nickel, that is, the material of the metal anti-corrosion transition layer includes nickel. The soluble salt of nickel includes, for example, one or more combinations of nickel sulfate, nickel sulfamate, or nickel chloride, but is not limited thereto.
[0037] In some embodiments, the first acid includes one or more of sulfuric acid, hydrochloric acid, or nitric acid.
[0038] In some embodiments, the surfactant includes one or a combination of sodium lauryl sulfate, sodium ethylhexyl sulfate or polyethylene glycol.
[0039] In some embodiments, the process conditions of the first electrodeposition include: a current density of 5-20 A / dm 2 , temperature is 30~50℃, time is 30~600s.
[0040] In some embodiments, the first anode is made of nickel, such as high-purity nickel.
[0041] In some embodiments, the step of coating the first intermediate material with a polymer microsphere composite metal layer specifically includes: using the first intermediate material as a second cathode and placing it together with a second anode in a second electroplating solution for a second electrodeposition reaction, wherein the second electroplating solution includes a soluble salt of a second metal, a second acid and polymer microspheres.
[0042] In some embodiments, the second electroplating solution contains 2-20 wt % of a soluble salt of a second metal, 5-20 wt % of a second acid, and 1-20 g / L of polymer microspheres.
[0043] In some embodiments, the soluble salt of the second metal includes a soluble salt of copper, that is, the material of the finally formed metal porous layer includes copper. The soluble salt of copper includes, for example, one or more of copper sulfate and copper chloride, but is not limited thereto.
[0044] In some embodiments, the second acid includes sulfuric acid and / or hydrochloric acid, but is not limited thereto.
[0045] In some embodiments, the process conditions of the second electrodeposition include: a current density of 0.5-20A / dm 2 , temperature is 30~40℃, time is 0.5~10h.
[0046] In some embodiments, the second anode is made of phosphor copper, but is not limited thereto.
[0047] In some embodiments, the preparation method further comprises pre-treating the metal mesh substrate to at least remove impurities and / or oil stains thereon.
[0048] In a typical embodiment, the method for preparing the gradient wetting multilayer metal mesh composite material comprises the following steps:
[0049] (1) Pre-treat the metal mesh substrate;
[0050] (2) immersing the pretreated metal mesh substrate and high-purity nickel in a nickel electroplating solution to form an electrochemical working system with the metal mesh substrate as a cathode and nickel as an anode, wherein the nickel electroplating solution comprises 5-25wt% nickel salt, 2-15wt% acid and 0.01-1wt% surfactant; connecting a power supply, applying a current with a current density of 5-20A / dm2 between the anode and the cathode, and performing an electrodeposition reaction at 30-50°C for 30-600 s to obtain a metal mesh having a nickel anti-corrosion transition layer, i.e., a first intermediate material;
[0051] (2) immersing the first intermediate material in a copper electroplating solution to form an electrochemical working system with the first intermediate material as a cathode and phosphor copper as an anode, wherein the copper electroplating solution comprises 2-20 wt% copper salt, 5-20 wt% acid and 1-20 g / L polystyrene microspheres; connecting a power source and applying a current density of 0.5-20 A / dm between the anode and the cathode; 2 The current is 0.5-10 hours at 30-40°C for electrodeposition reaction, and a polystyrene microsphere composite copper plating layer is formed on the first intermediate material to obtain a second intermediate material;
[0052] (3) The second intermediate material is placed in a muffle furnace and sintered at a temperature of 300-700° C. for 30-300 min to remove the polystyrene microspheres and simultaneously generate super-hydrophilic copper oxide on the surface of the copper coating and the inner wall of the pores to obtain a gradient wetting multilayer metal mesh composite material.
[0053] In some embodiments, the metal anticorrosion transition layer is nickel, the polymer in the polymer microsphere composite metal layer is polystyrene, and the metal is copper. On the one hand, this combination has good corrosion resistance, thermal conductivity, and excellent bonding between the layers. On the other hand, it is also specially selected considering the ease of removing the polymer microspheres under the premise of ensuring the stable existence of the composite material during high-temperature sintering, and the super hydrophilicity of copper after conversion to copper oxide. This is a preferred embodiment of the present invention. In particular, when the metal mesh substrate is made of stainless steel, the nickel layer formed by electrodeposition can improve the bonding between the metal mesh substrate and the porous copper layer.
[0054] The third object of the present invention is to provide the application of any of the gradient wetting multilayer metal mesh composite materials or the gradient wetting multilayer metal mesh composite materials prepared by any of the methods described in the preparation of heat spreader wicks or oil-water separation.
[0055] A fourth object of the present invention is to provide a heat spreader, comprising a shell and a liquid absorbent core arranged inside the shell, wherein the liquid absorbent core comprises the gradient wetting multi-layer metal mesh composite material described in any one of items or the gradient wetting multi-layer metal mesh composite material prepared according to any one of the methods described in any one of items.
[0056] Compared with the prior art, the present invention has at least the following beneficial effects:
[0057] (1) The composite material provided by the present invention has high porosity, good corrosion resistance, good hydrophilicity, excellent water storage capacity and capillary capacity. The functional layers complement each other and have multifunctional coupling, forming a gradient wetting structure from the surface to the inside of the material, which is suitable for the preparation of heat plate wicks, oil-water separation and other fields;
[0058] (2) The water contact angle of the composite material surface provided by the present invention can reach 0°; the flux of oil-water emulsion separation using the composite material can reach 1500 The separation efficiency is above 99.3%; the temperature difference between any two points on the surface of the heat spreader assembled with the liquid absorbent core prepared by the method is within 3°C. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0060] Figure 1 is a multilayer structure diagram of a gradient wetting multilayer metal mesh composite material in one embodiment of the present invention;
[0061] Figure 2 is a SEM image of the surface of the gradient wetting multilayer metal mesh composite material in Example 1 of the present invention;
[0062] Figure 3 This is a picture of the water contact angle on the surface of the gradient wetting multi-layer metal mesh composite material in Example 1 of the present invention. DETAILED DESCRIPTION
[0063] The technical solution of the present invention is described in detail below in conjunction with specific embodiments so that those skilled in the art can better understand and implement the technical solution of the present invention. The specific functional details disclosed herein should not be interpreted as being restrictive, but only as the basis for the claims and as a representative basis for teaching those skilled in the art to adopt the present invention in different ways in any appropriate detailed embodiment. The raw materials and reagents used in the following specific embodiments of the present invention are commercially available unless otherwise specified; the experimental methods in the following specific embodiments where specific conditions are not specified are generally carried out under conventional conditions.
[0064] Example 1
[0065] This embodiment provides a gradient wetting multi-layer metal mesh composite material. Figure 1 A schematic diagram of its structure is shown below.
[0066] The metal mesh substrate used in this embodiment is made of stainless steel with a mesh size of 120. The metal mesh substrate is pretreated, and the pretreatment steps are: immersing the metal mesh in a 30wt% sodium hydroxide solution at 80°C for 5 minutes, and then ultrasonically cleaning it with deionized water for 5 minutes;
[0067] The pretreated metal mesh and high-purity nickel are immersed in a nickel electroplating solution to form an electrochemical working system with the metal mesh as the cathode and nickel as the anode, wherein the solvent of the nickel electroplating solution is deionized water and contains 5wt% nickel sulfate, 2wt% sulfuric acid and 0.01wt% sodium dodecyl sulfate; a power supply is turned on and a current density of 5A / dm is applied between the anode and the cathode. 2The current was 0.04 and the electrodeposition reaction was carried out at 30°C for 600 s to obtain a metal mesh with a nickel anti-corrosion transition layer, which was recorded as the first intermediate material;
[0068] The first intermediate material obtained above and the phosphor copper sheet are immersed in a copper electroplating solution to form an electrochemical working system with a metal mesh having a nickel transition layer as a cathode and phosphor copper as an anode, wherein the solvent of the copper electroplating solution is deionized water and contains 2wt% copper sulfate, 5wt% sulfuric acid and 1g / L polystyrene microspheres with a particle size of 50nm; a power supply is turned on and a current density of 0.5A / dm is applied between the anode and the cathode. 2 The current was 1000 and the electrodeposition reaction was carried out at 30°C for 10 hours, and a copper plating layer with polystyrene microspheres was formed on the surface of the nickel transition layer, which was recorded as the second intermediate material.
[0069] The second intermediate material is placed in a muffle furnace and sintered at 300°C for 300 minutes to remove the polystyrene microspheres therein to form a porous copper layer with a micro-nano porous structure, while generating super-hydrophilic copper oxide on the surface of the porous copper layer to obtain a gradient wetting multilayer metal mesh composite material. Figure 2 This is a SEM picture of the surface of the gradient wetting multilayer metal mesh composite material obtained in Example 1.
[0070] The thickness of the metal mesh substrate in the composite material is 50 μm, the thickness of the nickel transition layer is 10 μm, the thickness of the porous copper layer is 200 μm, and the thickness of the copper oxide layer on the surface of the porous copper layer is 2 μm. The average pore size of the micro-nano porous structure of the porous copper layer is about 50 nm, and the inner wall of the pores contained in the micro-nano porous structure also has super-hydrophilic copper oxide, and the thickness of the copper oxide on the inner wall of the pores is about 2 μm.
[0071] Figure 3 is the water contact angle of the surface of the gradient wetting multilayer metal mesh composite material. The water contact angle of the surface of the composite material prepared in this embodiment is 0°.
[0072] Copper sheets were used as the upper and lower covers of the vapor chamber, and the composite material prepared above was used as a liquid wick package to obtain a vapor chamber. Under the test power condition of 5W, the temperature difference between any two points on the surface of the vapor chamber was less than 3°C.
[0073] The oil-water emulsion separation performance of the gradient wetting multilayer metal mesh composite material was tested, and the measured flux was 1500 , the separation efficiency is 99.3%.
[0074] Example 2
[0075] The metal mesh substrate used in this embodiment is copper with a mesh size of 500 meshes. The metal mesh substrate is pretreated, and the pretreatment steps are: immersing the metal mesh in a 30wt% sodium hydroxide solution at 80°C for 5 minutes, and then ultrasonically cleaning it with deionized water for 5 minutes;
[0076] The pretreated metal mesh and high-purity nickel are immersed in a nickel electroplating solution to form an electrochemical working system with the metal mesh as the cathode and nickel as the anode, wherein the solvent of the nickel electroplating solution is deionized water and contains 25wt% nickel chloride, 15wt% hydrochloric acid and 1wt% sodium ethylhexyl sulfate; a power supply is turned on and a current density of 20A / dm is applied between the anode and the cathode. 2 The current was 0.05 and the electrodeposition reaction was carried out at 50°C for 30 s to obtain a metal mesh with a nickel anti-corrosion transition layer, which was recorded as the first intermediate material;
[0077] The first intermediate material obtained above and the phosphor copper sheet are immersed in a copper electroplating solution to form an electrochemical working system with a metal mesh wrapped with a nickel plated layer as a cathode and phosphor copper as an anode, wherein the solvent of the copper electroplating solution is deionized water and contains 20wt% copper chloride, 20wt% hydrochloric acid and 20g / L polystyrene microspheres with a particle size of 1000nm; a power supply is turned on, and a current density of 20A / dm is applied between the anode and the cathode. 2 The current was 0.5 h at 30 °C, and the electroplating reaction was performed to generate a copper plating layer with polystyrene microspheres on the surface of the nickel transition layer, which was recorded as the second intermediate material.
[0078] The second intermediate material is placed in a muffle furnace and sintered at 700°C for 30 minutes to remove the polystyrene microspheres therein to form a porous copper layer with a micro-nano porous structure, while generating super-hydrophilic copper oxide on the surface of the porous copper layer to obtain a gradient wetting multilayer metal mesh composite material.
[0079] The thickness of the metal mesh substrate in the composite material is 200 μm, the thickness of the nickel transition layer is 50 μm, the thickness of the porous copper layer is 100 μm, and the thickness of the copper oxide layer on the surface of the porous copper layer is 10 μm. The average pore size of the micro-nano porous structure of the porous copper layer is about 1000 nm, and the inner wall of the pores contained in the micro-nano porous structure also has super-hydrophilic copper oxide, and the thickness of the copper oxide on the inner wall of the pores is about 40 μm.
[0080] According to tests, the water contact angle of the surface of the composite material prepared in this embodiment is 0°.
[0081] Copper sheets were used as the upper and lower covers of the vapor chamber, and the composite material prepared above was used as a liquid wick package to obtain a vapor chamber. Under the test power condition of 5W, the temperature difference between any two points on the surface of the vapor chamber was less than 3°C.
[0082] The oil-water emulsion separation performance of the gradient wetting multilayer metal mesh composite material was tested, and the measured flux was 1760 , the separation efficiency is 99.9%.
[0083] Example 3
[0084] The metal mesh substrate used in this embodiment is iron with a mesh size of 300 meshes. The metal mesh substrate is pretreated, and the pretreatment steps are: immersing the metal mesh in a 30wt% sodium hydroxide solution at 80°C for 5 minutes, and then ultrasonically cleaning it with deionized water for 5 minutes;
[0085] The pretreated metal mesh and high-purity nickel are immersed in a nickel electroplating solution to form an electrochemical working system with the metal mesh as the cathode and nickel as the anode, wherein the solvent of the nickel electroplating solution is deionized water and contains 15wt% nickel sulfamate, 8wt% nitric acid and 0.3wt% sodium dodecyl sulfate; a power supply is turned on and a current density of 10A / dm is applied between the anode and the cathode. 2 The current was 0.04 and the electrodeposition reaction was carried out at 40°C for 300 s to obtain a metal mesh with a nickel anti-corrosion transition layer, which was recorded as the first intermediate material;
[0086] The first intermediate material obtained above and the phosphor copper sheet are immersed in a copper electroplating solution to form an electrochemical working system with a metal mesh having a nickel transition layer as a cathode and phosphor copper as an anode; wherein the solvent of the copper electroplating solution is deionized water and contains 10wt% copper sulfate, 10wt% hydrochloric acid and 5g / L polystyrene microspheres with a particle size of 300nm; a power supply is turned on and a current density of 5A / dm is applied between the anode and the cathode. 2 The current was 1000 and the electrodeposition reaction was carried out at 30°C for 1 hour, and a copper plating layer having polystyrene microspheres was formed on the surface of the nickel transition layer, which was recorded as the second intermediate material.
[0087] The second intermediate material is placed in a muffle furnace and sintered at 500°C for 60 minutes to remove the polystyrene microspheres therein to form a porous copper layer with a micro-nano porous structure, while generating super-hydrophilic copper oxide on the surface of the porous copper layer to obtain a gradient wetting multilayer metal mesh composite material.
[0088] The thickness of the metal mesh substrate in the composite material is 100 μm, the thickness of the nickel transition layer is 10 μm, the thickness of the porous copper layer is 50 μm, and the thickness of the copper oxide layer on the surface of the porous copper layer is 5 μm; the average pore size of the micro-nano porous structure of the porous copper layer is about 300 nm, and the inner wall of the pores contained in the micro-nano porous structure also has super-hydrophilic copper oxide, and the thickness of the copper oxide on the inner wall of the pores is 12 μm.
[0089] According to tests, the water contact angle of the surface of the composite material prepared in this embodiment is 0°.
[0090] Copper sheets were used as the upper and lower covers of the vapor chamber, and the composite material prepared above was used as a liquid wick package to obtain a vapor chamber. Under the test power condition of 5W, the temperature difference between any two points on the surface of the vapor chamber was less than 3°C.
[0091] The oil-water emulsion separation performance of the gradient wetting multilayer metal mesh composite material was tested, and the flux was measured to be 1640 , the separation efficiency is 99.8%.
[0092] Example 4
[0093] The metal mesh substrate used in this embodiment is chromium, with a mesh size of 200 meshes. The metal mesh substrate is pretreated, and the pretreatment steps are: immersing the metal mesh in a 30wt% sodium hydroxide solution at 80°C for 5 minutes, and then ultrasonically cleaning it with deionized water for 5 minutes;
[0094] The pretreated metal mesh and high-purity nickel are immersed in a nickel electroplating solution to form an electrochemical working system with the metal mesh as the cathode and nickel as the anode, wherein the solvent of the nickel electroplating solution is deionized water and contains 5wt% nickel sulfamate, 10wt% nickel sulfate, 8wt% nitric acid and 0.1wt% sodium dodecyl sulfate; a power supply is turned on and a current density of 15A / dm is applied between the anode and the cathode. 2 The current was 0.04 and the electrodeposition reaction was carried out at 40°C for 300 s to obtain a metal mesh with a nickel anti-corrosion transition layer, which was recorded as the first intermediate material;
[0095] The first intermediate material obtained above and the phosphor copper sheet are immersed in a copper electroplating solution to form an electrochemical working system with a metal mesh having a nickel transition layer as a cathode and phosphor copper as an anode, wherein the solvent of the copper electroplating solution is deionized water and contains 5wt% copper sulfate, 5wt% copper chloride, 5wt% sulfuric acid, 5wt% hydrochloric acid and 10g / L polystyrene microspheres with a particle size of 500nm; a power supply is turned on, and a current density of 10A / dm is applied between the anode and the cathode. 2 The current was 0.8 h at 30°C, and a copper plating layer with polystyrene microspheres was formed on the surface of the nickel transition layer, which was recorded as the second intermediate material.
[0096] The second intermediate material is placed in a muffle furnace and sintered at 600°C for 80 minutes to remove the polystyrene microspheres therein to form a porous copper layer with a micro-nano porous structure, while generating super-hydrophilic copper oxide on the surface of the porous copper layer to obtain a gradient wetting multilayer metal mesh composite material.
[0097] The thickness of the metal mesh substrate in the composite material is 60 μm, the thickness of the nickel transition layer is 20 μm, the thickness of the porous copper layer is 100 μm, and the thickness of the copper oxide layer on the surface of the porous copper layer is 20 μm; the average pore size of the micro-nano porous structure of the porous copper layer is about 500 nm, and the inner wall of the pores contained in the micro-nano porous structure also has super-hydrophilic copper oxide, and the thickness of the copper oxide on the inner wall of the pores is about 2 μm.
[0098] According to tests, the water contact angle of the surface of the composite material prepared in this embodiment is 0°.
[0099] Copper sheets were used as the upper and lower covers of the vapor chamber, and the composite material prepared as above was used as the liquid wick package to obtain the vapor chamber. Under the test power condition of 5W, the temperature difference between any two points on the surface of the vapor chamber was less than 3°C.
[0100] The oil-water emulsion separation performance of the gradient wetting multilayer metal mesh composite material was tested, and the flux was measured to be 1980 , the separation efficiency is 99.7%.
[0101] Comparative Example 1
[0102] The control example 1 is basically the same as the example 1, except that the nickel transition layer is not constructed, and the porous copper layer is directly deposited on the stainless steel metal mesh substrate. Due to the lack of the nickel transition layer, the adhesion between the porous copper plating layer and the stainless steel substrate is poor, and a complete composite material cannot be obtained.
[0103] Comparative Example 2
[0104] Comparative Example 2 is substantially the same as Example 1, except that no porous copper plating layer is constructed, that is, the composite material formed only includes a metal mesh substrate and a nickel layer coated on the metal mesh substrate. The composite material does not have super hydrophilicity.
[0105] Comparative Example 3
[0106] Comparative Example 3 is substantially the same as Example 1, except that no sintering treatment is performed, that is, the hydrophilicity test is performed using the second intermediate material of Example 1.
[0107] Since no sintering treatment was performed, the copper in the copper plating layer composited with polystyrene microspheres could not be converted into hydrophilic copper oxide, so the hydrophilicity of the composite material was poor. The water contact angle of the surface of the composite material prepared in Control Example 3 was 70°, which did not achieve the super hydrophilic effect. In addition, the polystyrene microspheres were not removed by sintering treatment, so the formed composite material did not have the micro-nano porous structure described in the present invention, resulting in decreased water storage capacity, super hydrophilicity, and capillary capacity of the composite material.
[0108] Comparative Example 4
[0109] The difference between Comparative Example 4 and Example 1 is that the copper electroplating solution does not contain polystyrene microspheres, as follows:
[0110] The metal mesh substrate used in this embodiment is made of stainless steel with a mesh size of 120. The metal mesh substrate is pretreated, and the pretreatment steps are: immersing the metal mesh in a 30wt% sodium hydroxide solution at 80°C for 5 minutes, and then ultrasonically cleaning it with deionized water for 5 minutes;
[0111] The pretreated metal mesh and high-purity nickel are immersed in a nickel electroplating solution to form an electrochemical working system with the metal mesh as the cathode and nickel as the anode, wherein the solvent of the nickel electroplating solution is deionized water and contains 5wt% nickel sulfate, 2wt% sulfuric acid and 0.01wt% sodium dodecyl sulfate; a power supply is turned on and a current density of 5A / dm is applied between the anode and the cathode. 2 The current was 0.04 and the electrodeposition reaction was carried out at 30°C for 600 s to obtain a metal mesh with a nickel anti-corrosion transition layer, which was recorded as the first intermediate material;
[0112] The first intermediate material and the phosphor copper sheet obtained above are immersed in a copper electroplating solution to form an electrochemical working system with a metal mesh having a nickel transition layer as a cathode and phosphor copper as an anode, wherein the solvent of the copper electroplating solution is deionized water and contains 2wt% copper sulfate and 5wt% sulfuric acid; a power supply is turned on and a current density of 0.5A / dm is applied between the anode and the cathode. 2 The current was 10000 and the electrodeposition reaction was carried out at 30°C for 10 hours to form a copper plating layer on the surface of the nickel transition layer, which was recorded as the second intermediate material;
[0113] The second intermediate material is placed in a muffle furnace and sintered at 300° C. for 300 minutes to convert the copper on the surface of the porous copper layer into super-hydrophilic copper oxide to obtain a composite material.
[0114] The composite material obtained in Control Example 4 does not have the micro-nano porous structure described in the present application, and only the surface layer is hydrophilic and cannot store water, resulting in no oil-water separation performance, and the temperature difference of the heat spreader formed by using it to prepare the liquid wick is large.
[0115] In summary, the present invention uses a metal mesh as a carrier, and forms a metal anti-corrosion transition layer and a metal porous layer with a micro-nano porous structure on the carrier through electrodeposition technology combined with high-temperature sintering; the metal mesh with the metal anti-corrosion transition layer has good corrosion resistance and stable chemical properties, so that the composite material has a long service life; heating and sintering are used to remove the polymer microspheres to form a micro-nano porous structure, and at the same time, super-hydrophilic metal oxides are generated on the surface of the metal porous layer and the inner wall of the pores, thereby giving the composite material excellent water storage capacity and capillary capacity; the functional layers of the composite material provided by the present invention complement each other and are multifunctionally coupled to form a bottom-up gradient wetting structure, which can be used in the fields of heat spreader wicks, oil-water separation, etc.
[0116] In addition, the inventors of this case also conducted experiments with other raw materials and conditions listed in this specification in accordance with the methods of Examples 1 to 4, and finally obtained a gradient wetting multilayer metal mesh composite material with performance equivalent to that of Examples 1 to 4.
[0117] The various aspects, embodiments, features and examples of the present invention should be considered as illustrative in all aspects and are not intended to limit the present invention, the scope of the present invention is defined only by the claims. Other embodiments, modifications and uses will be apparent to those skilled in the art without departing from the spirit and scope of the claimed invention.
[0118] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.
[0119] Although the present invention has been described with reference to illustrative embodiments, it will be appreciated by those skilled in the art that various other changes, omissions and / or additions may be made without departing from the spirit and scope of the present invention and that the elements of the embodiments may be replaced by substantial equivalents. In addition, many modifications may be made without departing from the scope of the present invention to adapt specific circumstances or materials to the teachings of the present invention. Therefore, it is not intended herein to limit the present invention to the disclosed specific embodiments for performing the present invention, but it is intended that the present invention will include all embodiments within the scope of the appended claims. In addition, unless specifically stated, any use of the terms first, second, etc. does not indicate any order or importance, but rather uses the terms first, second, etc. to distinguish one element from another element.
Claims
1. A gradient wetting multilayer metal mesh composite material, characterized in that: include: A metal mesh substrate having a mesh structure formed of metal; A metal anti-corrosion transition layer is coated on the metal mesh substrate; A metal porous layer is covered on the metal anti-corrosion transition layer and has a micro-nano porous structure, and a super-hydrophilic metal oxide is distributed on the surface of the metal porous layer and the inner wall of the pores of the micro-nano porous structure, wherein the super-hydrophilic metal oxide is copper oxide; Among them, the thickness ratio of the metal mesh substrate and the metal anti-corrosion transition layer is 1~100:0.1~10, and the thickness ratio of the metal anti-corrosion transition layer to the metal porous layer is 0.1~10:1~20; the thickness ratio of the super hydrophilic metal oxide on the surface of the metal porous layer to the metal porous layer is 0.1~1:5~100.
2. The gradient wetting multilayer metal mesh composite material according to claim 1, characterized in that: The average pore size of the pores contained in the micro-nano porous structure is 50-1000 nm.
3. The gradient wetting multilayer metal mesh composite material according to claim 1, characterized in that: The porosity of the metal porous layer is 20-90%.
4. The gradient wetting multilayer metal mesh composite material according to claim 1, characterized in that: The diameter of the mesh contained in the metal mesh substrate is 120-500 meshes.
5. The gradient wetting multilayer metal mesh composite material according to claim 1, characterized in that: The material of the metal mesh substrate is stainless steel, or includes one or more of copper, iron, and chromium. The material of the metal anti-corrosion transition layer includes nickel. The material of the metal porous layer includes copper.
6. The gradient wetting multilayer metal mesh composite material according to claim 1, characterized in that: The contact angle between the surface of the gradient wetting multilayer metal mesh composite material and water is 0°.
7. A method for preparing a gradient wetting multilayer metal mesh composite material, characterized in that: include: Providing a metal mesh substrate, using the metal mesh substrate as a first cathode, and placing the metal mesh substrate together with a first anode in a first electroplating solution for a first electrodeposition reaction, wherein the first electroplating solution includes a soluble salt of a first metal, a first acid, and a surfactant, so as to form a metal anti-corrosion transition layer on the metal mesh substrate, and obtain a first intermediate material; The first intermediate material is used as a second cathode and placed together with a second anode in a second electroplating solution for a second electrodeposition reaction, wherein the second electroplating solution comprises 2-20 wt% of a soluble salt of a second metal, 5-20 wt% of a second acid and 1-20 g / L of polymer microspheres, wherein the soluble salt of the second metal is a soluble salt of copper, and the microspheres are made of polystyrene, so as to form a polymer microsphere composite metal layer on the first intermediate material to obtain a second intermediate material, wherein the polymer microsphere composite metal layer comprises a metal material layer and polymer microspheres, and the polymer microspheres are distributed on the surface and inside of the metal material layer; The current density of the second electrodeposition is 0.5-20A / dm 2 , temperature is 30~40℃, time is 0.5~10h; At least the second intermediate material is sintered to remove the polymer microspheres, forming a porous metal layer with a micro-nano porous structure, and simultaneously forming super-hydrophilic metal copper oxide on the surface of the porous metal layer and on the inner wall of the pores of the micro-nano porous structure, to obtain a gradient wetting multilayer metal mesh composite material.
8. The preparation method according to claim 7, characterized in that: The metal mesh substrate is made of stainless steel, or one or more of copper, iron, and chromium.
9. The preparation method according to claim 7, characterized in that: The particle size of the polymer microspheres is 50-1000 nm.
10. The preparation method according to claim 7, characterized in that: The sintering temperature is lower than the melting point of the metal in the metal mesh substrate, the metal anti-corrosion transition layer and the polymer microsphere composite metal layer, and can remove the polymer microspheres.
11. The preparation method according to claim 10, characterized in that: The process conditions of the sintering treatment include: a sintering temperature of 300-700° C. and a sintering time of 30-300 min.
12. The preparation method according to claim 7, characterized in that: The first electroplating solution contains 5-25 wt % of a soluble salt of a first metal, 2-15 wt % of a first acid, and 0.01-1 wt % of a surfactant.
13. The preparation method according to claim 7, characterized in that: The soluble salt of the first metal includes a soluble salt of nickel; and / or the first acid includes a combination of one or more of sulfuric acid, hydrochloric acid or nitric acid; and / or the surfactant includes a combination of one or more of sodium dodecyl sulfate, sodium ethylhexyl sulfate or polyethylene glycol.
14. The preparation method according to claim 7, characterized in that: The process conditions of the first electrodeposition include: a current density of 5-20A / dm 2 , temperature is 30~50℃, time is 30~600s.
15. The preparation method according to claim 7, characterized in that: The material of the first anode is nickel.
16. The preparation method according to claim 7, characterized in that: The soluble salt of the second metal includes a soluble salt of copper; and / or, the second acid includes sulfuric acid and / or hydrochloric acid; and / or, the material of the second anode is phosphor copper.
17. Use of the gradient wetting multilayer metal mesh composite material according to any one of claims 1 to 6 in preparing a vapor chamber wick or oil-water separation.
18. A vapor chamber, comprising a shell and a liquid wick disposed inside the shell, characterized in that: The liquid-absorbing core comprises the gradient wetting multi-layer metal mesh composite material according to any one of claims 1 to 6.
Citation Information
Patent Citations
Super-hydrophilic oleophobic material, preparation method and applications thereof
CN109381893A
Preparation method and device for super-hydrophilic copper-based compound material with controllable structure
CN115744961A